(untitled) (Revista de Estudios Teóricos y Epistemológicos en Política Educativa, 2023)
This article aims to analyze the contributions of Marx’s dialectical method to the understanding of reality, from the contradiction category in studies on the role of trade unions and their relationship with politics. This is a bibliographic study, based on Marx (2013), Trotsky (1980) and Benoit (1996, 1997, 1998, 2003, 2007, 2008). Supported by the studies carried out, we emphasize that considering the contradiction category and its immanentism in the dialectical materialist tradition is fundamental to understand the role of trade unions in the socialist revolution and to overcome the dichotomous interpretations of the economic struggle and the political struggle, especially for the understanding of the struggle of classes as a historical process, contradictory and promoter of its own negation. Within the scope of teacher unionism and educational policy, the dialectical contradiction contributes to the understanding of the limits and possibilities that originate from this relationship, since the approximation of the teachers’ struggle with educational policies represents an advance in the perspective of the legislation of the teaching career and, contradictorily, limits trade unionism to the rhythm of state policies. Keywords: Historical-dialectical materialism. Contradiction. Method. Unions.